Implementation of multicultural education values in the learning process in grade V elementary school - Akbarwati, Putri; Supriyanto, Teguh; Trimurtini, Trimurtini (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Indonesia is a country that has a wide range of diversity in language, religion, culture, ethnicity, and customs. Diversity can trigger differences that have a negative impact, if not balanced with tolerance. Tolerance must be introduced early so that students have character values that can provide for the future. This research aims to analyze the role of teachers in applying the value of multicultural education in the learning process and the importance of instilling the value of multicultural education in students. The research method used is the descriptive qualitative method. The data collection techniques used were observation, interview, and documentation until triangulation. The data analysis technique used refers to the Miles & Huberman theory, namely with the stages of data collection, data reduction, data presentation, and conclusions/verification. The results of this study show that the implementation of multicultural education values can be done through habituation activities of character values in students that are arranged in the teacher's strategy.